Physio-biochemical Changes in Sorghum Cultivars under Different Moisture Regimes - Pawar B, Sujata; S. R, Gagakh (International Journal of Bio-resource and Stress Management, 2023)
An experiment was conducted to evaluate the effects of water deficit on physio-biochemical and yield parameters on sorghum during rabi season (September 2009 to February 2010) in Maharashtra. The treatment combinations consisted of four moisture regimes viz., M1, M2, M3 and M4 upto harvest and six genotypes viz., Phule Yashoda, RSV-1006, Phule Chitra, Phule Vasuda, Phule Anuradha, Phule Maulee. The study revealed that, Phule Yashoda and Phule Revati genotypes had maximum mean growth parameters and hence had maximum yield and yield contributing characters at lower moisture regime M1 than non-stress condition M4. RSV-1006 and Phule Chitra genotypes had maximum total soluble sugar content. The proline content increased with a decrease in the soil moisture content in all the genotypes with predominance in Phule Maulee, Phule Chitra and Phule Anuradha which also reported positive correlation of proline accumulation with grain yield. The degree of reduction in protein content as a function of water stress was less in Phlule Maulee, Phule Chitra and Phule Anuradha respectively. The genotypes Phlule Maulee, Phule Chitra and Phule Anuradha had lowest nitrate reductase activity under moisture regime M1. Among the six genotypes, Phule Yashoda and Phule Revati showed higher grain yield and yield contributing parameters. The present study revealed that genotypes Phule Chitra and Phule Maulee are more suited under limited soil moisture condition. Irrespective of moisture regime Phule Yashoda and RSV-1006 found better than rest of genotypes. Therefore, these genotypes are well suited for medium soil under stress as well as non-stress conditions.